Harlequin Icthyosis: A Rare Disorder (Indian Journal of Case Reports, 2016)
Harlequin ichthyosis (HI) is the rarest and the most severe form of congenital ichthyosis. It is inherited in an autosomal recessive manner and associated with mutations in gene ABCA12. There have been reports of several families with siblings affected with harlequin icthyosis. Affected infants have severe ectropion, eclabium, diffuse decreased range of motion, thick, dry hyperkeratotic plates, over entire body and scalp and associated deep erythematous fissures. Infants with HI have historically succumbed in the perinatal period to sepsis, respiratory failure and infections, poor nutrition and electrolyte imbalances. It is a rare entity. We report here a case of harlequin Icthyosis infant born to consanguineous parents whose 3 siblings were also affected with the same disorder.